О жизненном цикле офиотении европейской — Ophiotaenia europaea Оdеning, 1963 (Cesloda, Ophiotaeniidae) - Шарпило, В.П.; Монченко, В.И. (Вестник зоологии, 1971)
It is proved by experiment that three hosts — intermediate (cyclops), additional (amphibians) and final (snakes) participate in the life cycle of cestode Ophiotaenia europaea Odening , 1963. A list of host species for each group is given.